Analisis Pendekatan Komunikasi Partisipatif Lembaga Desa dalam Pemberdayaan Masyarakat Untuk Pembangunan Berkelanjutan - S. Kaseng, Ernawati (Research Agency for Humanity and Urban, 2023)
This research aims to analyze the role of village institutions in community empowerment through a participatory communication approach. Participatory communication is considered an effective strategy to involve the community in decision-making and the implementation of empowerment programs. The research method employed is a qualitative approach, utilizing in-depth interviews, participatory observation, and document analysis. The findings indicate that village institutions play a crucial role in community empowerment efforts. Through the participatory communication approach, the community actively engages in the planning, execution, and evaluation of empowerment programs. Community participation enhances their understanding of local needs, fosters a sense of ownership over the programs, and improves implementation effectiveness. In conclusion, village institutions play a significant role in promoting community empowerment through participatory communication. Active community involvement in decision-making and program implementation makes empowerment more relevant and sustainable. Therefore, efforts to enhance the capacity of village institutions and strengthen participatory communication mechanisms are necessary to achieve more optimal outcomes in community empowerment endeavors.